Floating exchange rates at fifty - A. Irwin,Douglas (Congresses., 2024)
"Fifty years ago, in March 1973, the major industrial economies abandoned fixed exchange rates based on gold, conclusively ending the post-World War II Bretton Woods arrangements. Proponents believed their action would strengthen countries' ability to deal with balance of payment problems. But opponents feared it would instigate a new era of instability and financial shocks. Since 1973, the world has moved away from fixed exchange rates to intermediate regimes based on considerable exchange rate flexibility. But international trade conflicts and unstable capital flows, along with a rise in financial crises around the world, have nonetheless accompanied the global shift away from exchange rate pegs. How has the international monetary system performed over the past half century-if it can even be called a "system"? What have we learned from the experience of more flexible exchange rates? What has been the impact on macroeconomic and financial stability in the years since? This conference brought together leading economists and policymakers to debate and discuss these questions, as well as to think about the evolution of the international monetary system, the dominance of the US dollar, and the role of exchange rate regimes in shaping the world economy"--